Origin and development of special economic knowledge in world system of the criminal - a procedural law. Historical aspect - K. V. Tishkin (Путеводитель предпринимателя)
The article discusses the nature of the institution «special economic knowledge», as well as issues of its practical application for the purposes of criminal proceedings. By listing its attributes, proposed an alternative definition of the concept.